Mental Health Care for helpers: Experiences from a Training Programme - Ajduković, Marina (Array, 1998)
The Society for Psychological Assistance, a Zagreb-based mental health NGO, started a training project in the spring of 1994, aimed at meeting the mental health need of helpers. The goal of the project was to develop and implement a training programme for self-management and self-empowerment of care providers in order to prevent their burnout and secondary traumatisation. Practical assistance was given to 57 helpers in two three-day workshops; a manual was prepared, and the outcomes of the workshop was evaluated. Three groups of stress sources were identified by participants of the training programme. One group was dependent upon personality, another group comprised environmental sources (working conditions, relationships with other people in the team and organisation of work), and the third group included specific characteristics of humanitarian work. Both the verbal feedback received during and after the programme, and the written anonymous evaluation showed that the programme was well received and that it met an existing need. The participants reported improved relations with colleagues, greater capacity for defining their limits at work, less exhaustion, better communication among group members.